Perancangan User Experience Aplikasi Pengajuan E-KTP menggunakan Metode UCD pada Kelurahan Tanah Baru - Sarfina Luthfiyah Ramadhan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Electronic KTP is a public document that has a security or control system in terms of management and information technology-based on national data. In this digital era, the Tanah Baru Urban Village Office is still providing services for making ID cards manually. This is considered inefficient because applicants have to queue and wait a long time until the KTP process is complete. Lack of labor force made the process of making a KTP take quite a long time. The result of this research is to apply the user-centered design method to the application system for making electronic ID cards. The advantage of the UCD method is to build an application system for making E-KTP applications with a high level of efficiency and is easy to use because the UCD method involves the user in the entire design process. Keywords— Information System, User Experience, User Centered Designv